USE OF ANTIBIOTICS IN HIP AND KNEE ARTHROPLASTY AND PREVENTION OF INFECTIOUS COMPLICATIONS. (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Arthroplasty is also a very traumatic procedure, and in some cases, it is characterized by significant blood loss. In the postoperative period, venous thrombosis and thromboembolism of pulmonary arteries (PETE) are the most dangerous [110; 101-106-b, 109; 1018-1025-b, 46; p. 455-461].Based on the above, anesthesia can completely block nociceptive impulses, minimize postoperative blood loss and the need for donor blood and blood components, the development of thromboembolic complications in the postoperative period, and obvious postoperative pain. reducing the likelihood of Rick's syndrome should be consistent with the nature of this intervention. [11; p. 210-212]. Central segmental blockade methods maximally meet all these requirements [61; 810-814-b, 136; p. 193-199].There are more different types of local anesthetic (SA, EA, joint SEA, transfer) than the methods of anesthesia used in endoprosthesis of leg joints [10; p. 16-21, 154; pp. 360-364, 108; 774-781-p], and the method of general anesthesia is used relatively little [6; p. 85-90, 157; p. 5-14].Conventional general anesthesia, which eliminates pain perception (perception), leads to the release of neuropeptides and excitatory amino acids without interfering with nociceptive stimulation of central structures. This, in turn, leads to the development of a lack of inhibitory control, which causes the sensitivity of the dorsal branches of the spinal cord, which leads to their sustained depolarization and the emergence of postoperative pain syndrome [25; p. 5-12]. At the same time, we cannot but agree with the view that modern strong inhalation anesthetics during surgery only create the illusion of adequate anesthesia and manifest as an effect on the most proximal joint of the formation of acute pain syndrome. [27; p. 93-105].